Crisis? What crisis? Currency vs. banking in the Financial Crisis of 1931 - Albrecht Ritschl; Samad Sarferaz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
This paper examines the role of currency and banking in the German financial crisis of 1931 for both Germany and the U.S. We specify a structural dynamic factor model to identify financial and monetary factors separately for each of the two economies. We find that monetary transmission through the Gold Standard played only a minor role in causing and propagating the crisis, while financial distress was important. We also find evidence of crisis propagation from Germany to the U.S. via the banking channel. Banking distress in both economies was apparently not endogenous to monetary policy. Results confirm Bernanke's (1983) conjecture that an independent, non-monetary financial channel of crisis propagation was operative in the Great Depression.
Keywords: N12; N13; E37; E47; C53; 330; Great Depression; 1931 financial crisis; international business cycle transmission; Bayesian factor analysis; currency; banking; Finanzmarktkrise; Währungspolitik; Bankenliquidität; Goldwährung; Geldpolitik; Transmissionsmechanismus; Wirtschaftsgeschichte; Deutschland; USA